VD_FINDINFO HC / 2013 / 617 vom 26. August 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, DROIT DE LA FAMILLE, OBLIGATION D'ENTRETIEN, NOUVEAU MOYEN DE FAIT | 176 al. 1 ch. 1 CC, 248 let. d CPC (CH), 308 CPC (CH), 317 al. 1 CPC (CH)